2014
DOI: 10.1016/j.enpol.2014.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy policy instruments on the estimated level of underlying energy efficiency in the EU residential sector

Abstract: The Surrey Energy Economics Centre (SEEC) consists of members of the School of Economics who work on energy economics, environmental economics and regulation. The School of Economics has a long-standing tradition of energy economics research from its early origins under the leadership of Professor Colin Robinson. This was consolidated in 1983 when the University established SEEC, with Colin as the Director; to study the economics of energy and energy markets. SEEC undertakes original energy economics research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
124
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 21 publications
10
124
1
1
Order By: Relevance
“…In this respect, it has been argued that the contribution of technology in the framework of stochastic frontier can be indirectly captured by a number of factors, as for instance by the price and income effects (see Filippini and Hunt, 2012). More recently, Filippini et al (2014) introduced a specific variable to control the amount of wasted energy due to households not using the best available technologies, although admitting the limitations of this approach, such as the lack of data on consumers' behaviour, heterogeneity in the level of electricity consumption and the fact that such a method is not able to disentangle the energy saving deriving from a more efficient use of inputs or from the adoption of energy saving technologies.…”
Section: Disentangling Energy Efficiency From Energy Savingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, it has been argued that the contribution of technology in the framework of stochastic frontier can be indirectly captured by a number of factors, as for instance by the price and income effects (see Filippini and Hunt, 2012). More recently, Filippini et al (2014) introduced a specific variable to control the amount of wasted energy due to households not using the best available technologies, although admitting the limitations of this approach, such as the lack of data on consumers' behaviour, heterogeneity in the level of electricity consumption and the fact that such a method is not able to disentangle the energy saving deriving from a more efficient use of inputs or from the adoption of energy saving technologies.…”
Section: Disentangling Energy Efficiency From Energy Savingmentioning
confidence: 99%
“…They find inconsistency in several States between the standard energy intensity indicators and energy efficiency scores deriving from the stochastic frontier approach used in the analysis, suggesting further investigation on this direction. More recently, Filippini et al (2014) focus on the impact of government policies aimed at improving energy efficiency in the residential sector. Although the large number of in-force policy instruments existing in the EU, they find room for efficiency gains and a high level of variability across countries, although not significant differences between new and old EU Member States have been detected.…”
Section: Measuring Energy Efficiencymentioning
confidence: 99%
“…The dataset includes information on the level of energy services, which is usually not measured as it can be difficult to collect this information. 5 Information on the level of energy services is a critical issue when using SFA (Filippini et al, 2014). Finally, to our knowledge, this paper is the first one to provide a systematic analysis of the impact of both energy and investment literacy on the total electricity consumption of households while controlling for the effects of the general level of education of the household members.…”
mentioning
confidence: 99%
“…While the Stochastic Frontier Analysis (SFA) has been used with aggregated energy data (e.g., Filippini and Hunt (2012); Filippini et al (2014)), we use dis-aggregated data since residential consumers are typically very heterogeneous and household level data can add more detail to the knowledge of consumer response. Weyman-Jones et al (2015) are one of the first to estimate energy efficiency using SFA with dis-aggregated household survey data.…”
mentioning
confidence: 99%
“…Studies have revealed that 30% of CO 2 emissions in the EU are from buildings. Further, it has been found that the energy used in heating living spaces in residential buildings accounts for 57%, while that for water is about 25% of the entire energy used [1][2][3].…”
Section: Introductionmentioning
confidence: 99%